Pendidikan Islam Persepktif KH Hasyim Asy’ari dalam Menjaga Api Keislaman dan Kebangsaan - Fathul Amin; Sholikah Sholikah (Al Hikmah: Jurnal Studi Keislaman, 2022)
Abstract, KH M Hasyim Asy'ari is an Indonesian Islamic figure who has advantages in uniting Islam and Indonesianness. So that Muslims have a standard attitude in practicing Islam and as a state. Kiai Hasyim's thoughts are unique because they are continued by all of his descendants and the Tebuireng students. Two points that are characteristic of Kiai Hasyim's thought, namely Islam and Indonesianness, need to be spread on various social media platforms that are familiar to the younger generation. That way, the next generation of the nation can see clearly the thoughts of KH M Hasyim, Kiai Wahid Hasyim, Gus Dur and Salahuddin Wahid regarding Indonesianness and Islam. As for the real way that KH Hasyim Asy'ari did, namely: First, in starting an idea, KH Hasyim Asy'ari first showed it with his attitude and actions. Second, to base each of his thoughts on the substance of Islamic teachings originating from the Al-Qur'an and related hadiths; Third, KH Hasyim Asy'ari's specialty compared to other figures lies in his writing ability. KH Hasyim immortalized his thoughts in written form; Fourth, KH Hasyim Asy'ari educates biological and ideological children who continue his struggle; and Fifth, KH Hasyim Asy'ari organized and open with all groups. This is what makes KH Hasyim's thoughts accepted by many groups.